Social business: A new private sector contribution to development? Reflections on opportunities, limitations, and risks - Linda Kleemann; Kerstin Humberg (Kiel Institute for the World Economy (IfW), 2014)
Since Nobel Peace Laureate Muhammad Yunus first began launching joint ventures with multinational corporations (MNCs) in Bangladesh, his social business concept has received international attention. What's the meaning of social business? What can it contribute to poverty reduction, and how does it foster human development? With reference to empirical findings, we illustrate how social business enterprises can create new sources of income, raise productivity and provide low-income consumers with access to products for their basic needs. Yet the findings are not suggestive of a panacea. Social purpose business rather represents a complementary approach to traditional poverty reduction strategies with its own set of opportunities, limitations, and risks. Some of the limitations could be mitigated by means of cross-sector partnerships and development partners creating an enabling environment. The mitigation of risks, however, will require a deliberate regulatory framework and rigorous monitoring and evaluation of impact.
Keywords: 330